Answer: The correct option is
(B)
![f^(-1)(x)=(1)/(x-1).](https://img.qammunity.org/2020/formulas/mathematics/high-school/je0ch4n53twenqajy85pfabuwl5v70jqu4.png)
Step-by-step explanation: We are given to select the correct expression that is the inverse of the following function :
![f(x)=(x+1)/(x)~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)](https://img.qammunity.org/2020/formulas/mathematics/high-school/2zyk6z34g8pppus93rt6wxdde7b8tf38wp.png)
Let y denotes f(x). Then,
![y=f(x)~~~~~~\Rightarrow x=f^(-1)(y).](https://img.qammunity.org/2020/formulas/mathematics/high-school/oxvd8o0e8p2o7f23qq1zrm1z99j668qiti.png)
Substituting this value in equation (i), we get
![f(x)=(x+1)/(x)\\\\\\\Rightarrow y=(f^(-1)(y)+1)/(f^(-1)(y))\\\\\\\Rightarrow yf^(-1)(y)=f^(-1)(y)+1\\\\\Rightarrow yf^(-1)(y)-f^(-1)(y)=1\\\\\Rightarrow (y-1)f^(-1)(y)=1\\\\\Rightarrow f^(-1)(y)=(1)/(y-1)\\\\\Rightarrow f^(-1)(x)=(1)/(x-1).](https://img.qammunity.org/2020/formulas/mathematics/high-school/r2ib9a9xkd21pp5h48pk6jkd9jdmc5icb9.png)
Thus, the required inverse of the given function is
![f^(-1)(x)=(1)/(x-1).](https://img.qammunity.org/2020/formulas/mathematics/high-school/je0ch4n53twenqajy85pfabuwl5v70jqu4.png)
Option (B) is CORRECT.